BiFeO3(00l)/LaNiO3/Si thin films with enhanced polarization: an all-solution approach. Issue 82 (18th August 2016) - Jin, Linghua; Tang, Xianwu; Wei, Renhuai; Yang, Bingbing; Yang, Jie; Song, Wenhai; Dai, Jianming; Zhu, Xuebin; Sun, Yuping
Abstract : Multiferroic BiFeO3 (BFO) thin films with a thickness larger than 400 nm are grown on solution-derived LaNiO3 coated Si substrates via chemical solution deposition. Abstract : Multiferroic BiFeO3 (BFO) thin films with a thickness larger than 400 nm are grown on solution-derived LaNiO3 coated Si substrates via chemical solution deposition. The prepared BFO/LaNiO3 /Si thin films are strongly (00 l )-oriented with a distorted rhombohedral structure of R 3 c symmetry. The effects of the annealing temperature within the temperature range of 500–650 °C on the microstructures and properties are investigated. With an annealing temperature increasing to 600 °C, the (00 l ) orientation is enhanced and the grain size is increased, whereas a higher annealing temperature will lead to the deterioration of the orientation and microstructures. The annealing temperature dependent dielectric, leakage and ferroelectric properties are investigated, showing excellent properties for the low temperature annealed BFO thin films. The mechanisms about annealing temperature effects are discussed. The results will provide an effective route to realize the integration of large-area BFO thin films on Si wafers by an all-solution approach with low cost.